Temperature Effects on Nuclear Masses, Reactions and Abundances - Trujillo, José Daniel; Kelkar, N. G.; Nowakowski, M. (Revista de Ciencia y Tecnología, 2023)
Nuclear reactions occurring in astrophysical environments are influenced by the masses and energies of the nuclei involved, as well as the temperature of the surrounding environment. It is noteworthy to observe the relationship between the excitation energies of nuclei and the temperature of the environment in which the nuclei are present. Therefore, it is reasonable to consider the temperature dependence of masses in astrophysical environments. However, it is common in the literature to treat nuclear masses as constant regardless of temperature. In this study, we will explore the effects of temperature on nuclear masses and investigate how this variation impacts the relevant nuclear reaction rates in the context of big bang nucleosynthesis. By considering the temperature dependence of masses, we aim to gain a deeper understanding of the changes in reaction rates that occur in astrophysical scenarios.